Effective Modulation of CNS Inhibitory Microenvironment using Bioinspired Hybrid‐Nanoscaffold‐Based Therapeutic Interventions. Issue 43 (6th September 2020) - Yang, Letao; Conley, Brian M.; Cerqueira, Susana R.; Pongkulapa, Thanapat; Wang, Shenqiang; Lee, Jae K.; Lee, Ki‐Bum
Abstract: Central nervous system (CNS) injuries are often debilitating, and most currently have no cure. This is due to the formation of a neuroinhibitory microenvironment at injury sites, which includes neuroinflammatory signaling and non‐permissive extracellular matrix (ECM) components. To address this challenge, a viscous interfacial self‐assembly approach, to generate a bioinspired hybrid 3D porous nanoscaffold platform for delivering anti‐inflammatory molecules and establish a favorable 3D‐ECM environment for the effective suppression of the neuroinhibitory microenvironment, is developed. By tailoring the structural and biochemical properties of the 3D porous nanoscaffold, enhanced axonal growth from the dual‐targeting therapeutic strategy in a human induced pluripotent stem cell (hiPSC)‐based in vitro model of neuroinflammation is demonstrated. Moreover, nanoscaffold‐based approaches promote significant axonal growth and functional recovery in vivo in a spinal cord injury model through a unique mechanism of anti‐inflammation‐based fibrotic scar reduction. Given the critical role of neuroinflammation and ECM microenvironments in neuroinhibitory signaling, the developed nanobiomaterial‐based therapeutic intervention may pave a new road for treating CNS injuries. Abstract : Current biomaterials‐based treatment of central nervous system (CNS) injuries has been hampered by the resulting neuroinhibitory microenvironment. By targeting two critical neuroinhibitory factors in a single platform, a biomimetic 3D porous hybrid nanoscaffold is created by developing viscous interfacial self‐assembly. The nanoscaffold‐based therapeutic interventions achieve functional recovery through reducing neuroinflammation and fibrotic scarring, thereby paving a new road for the biomaterials‐based treatment of CNS injuries.